Tuberculous Meningoencephalitis in Lost To Follow-Up Patient: A Case Report - Graciela, Yemima; Wisnuwardhani, Dian; Hamdani, Ismi Adhanisa (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Tuberculous meningoencephalitis (TBME) is a rare extrapulmonary TB that accounted for less than 1-2% with high mortality and morbidity rate. Loss of follow-up (LTFU) TB cases are also associated with worse prognosis, treatment failure, drug-resistant cases, decompensations, and complications. The objective of this study is to present a TBME case in LTFU patient as both conditions are correlated with worse outcomes for the patient. Case report: A 20-year-old man with a history of discontinued TB therapy presented to the emergency room (ER) with complaints of depressed consciousness, absence seizure, fever, shivers, nausea, vomiting, and holo-cranial headache. The diagnosis of TBME was confirmed by contrast-enhanced radiological findings, detection of M. tuberculosis in sputum, and blood investigations. Early initiation of anti-tuberculous drugs was given and showed marked clinical improvement followed by complete relief after a month follow-up. Conclusion: TBME should be diagnosed in patients living in high-rate TB countries with presumptive symptoms and signs supported by laboratory investigations as well as radiological findings to initiate early treatment. LTFU patients should be monitored with family or social group support while improving TB regimens in healthcare facilities. Keywords: Tuberculosis, meningoencephalitis, loss-to-follow up